USING THE FACTOR GRAPH TO EVALUATE THE QUALITY OF OUTPUT DATA FOR SHIFT-DAILY LOADING PLANNING - Kamaletdinov, Shoxrux; Aripov, Nazirjon; Abdumalikov, Islomjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Assessing the quality of automated systems is a very difficult task. This article uses a factor graph and a message passing algorithm to evaluate the quality of the output of the automated local work management system (ALWMS). The proposed evaluation method makes it possible to take into account the impact of each element of the system on the output data.